Violations of Consular Protection and Their Impact on Algerian–European Relations During the Ottoman Era - Haddou, Sana (Journal of Ecohumanism, 2025)
Research on Algeria’s diplomatic sphere during the Ottoman period continues to attract scholars. This interest stems from the decisive role played by the Algerian navy in the western Mediterranean, a role that often led to confrontation or peace. Yet this field still requires more studies that deepen understanding, clarify its features, and shed light on hidden aspects of the era. One of the most important of these aspects is the diplomatic environment. Ottoman Algeria was a major diplomatic hub. It received envoys and consuls and concluded several treaties and agreements due to its position and influence in the region at the time. Consuls enjoyed many privileges to ensure their safety and the protection of their property. However, these immunities were frequently violated, which strained relations between Algeria and European states and at times led to the suspension of diplomatic ties.